"Blind leading the blind": Qualitative evaluation of unanticipated difficulties during nurse testing of a hospital health information system. Issue 1 (February 2020) - Bail, Kasia; Merrick, Eamon; Redley, Bernice; Gibson, Jo; Davey, Rachel; Currie, Marian
Abstract: Aim: To describe the self-reported experiences of clinicians evaluating a novel Health Information System in an acute care environment. Design: The Health Information System was implemented over a one-month period in 2017 into a 26-bed acute medical ward within a 760-bed tertiary teaching hospital in Australia. Methods: Data were collected using interviews with 48 multidisciplinary clinicians and 20 patients, and 2 focus groups with 13 nurses, and analysed with a 'content, context, and process' evaluation framework. Results: Three themes reflecting unanticipated difficulties emerged from the qualitative data: (1) inconsistent expectations; (2) decisional conflict between managers and end-user nurses; and (3) workflow impacts. Conclusions: Designers and evaluators of information systems must listen to, prioritise and respond to the needs of the clinicians who provide care.